Sex Differences in Primary and Secondary Prevention of Cardiovascular Disease in China - Xia, Shijun; Du, Xin; Guo, Lizhu; Du, Jing; Arnott, Clare; Lam, Carolyn S P; Huffman, Mark D; Arima, Hisatomi; Yuan, Yiqiang; Zheng, Yang; Wu, Shulin; Guang, Xuefeng; et al. (Circulation (New York, N.Y.), 2020)
Despite improvements in diagnostic and therapeutic interventions to combat cardiovascular disease (CVD) in recent decades, there are significant ongoing access gaps and sex disparities in prevention that have not been adequately quantified in China. A representative, cross-sectional, community-based survey of adults (aged ≥45 years) was conducted in 7 geographic regions of China between 2014 and 2016. Logistic regression models were used to determine sex differences in primary and secondary CVD prevention, and any interaction by age, education level, and area of residence. Data are presented as adjusted odds ratios (ORs) and 95% CIs. Of 47 841 participants (61.3% women), 5454 (57.2% women) had established CVD and 9532 (70.5% women) had a high estimated 10-year CVD risk (≥10%). Only 48.5% and 48.6% of women and 39.3% and 59.8% of men were on any kind of blood pressure (BP)-lowering medication, lipid-lowering medication, or antiplatelet therapy for primary and secondary prevention, respectively. Women with established CVD were significantly less likely than men to receive BP-lowering medications (OR, 0.79 [95% CI, 0.65-0.95]), lipid-lowering medications (OR, 0.69 [95% CI, 0.56-0.84]), antiplatelets (OR, 0.53 [95% CI, 0.45-0.62]), or any CVD prevention medication (OR, 0.62 [95% CI, 0.52-0.73]). Women with established CVD, however, had better BP control (OR, 1.31 [95% CI, 1.14-1.50]) but less well-controlled low-density lipoprotein cholesterol (OR, 0.66 [95% CI, 0.57-0.76]), and were less likely to smoke (OR, 13.89 [95% CI, 11.24-17.15]) and achieve physical activity targets (OR, 1.92 [95% CI, 1.61-2.29]). Conversely, women with high CVD risk were less likely than men to have their BP, low-density lipoprotein cholesterol, and bodyweight controlled (OR, 0.46 [95% CI, 0.38-0.55]; OR, 0.60 [95% CI, 0.52-0.69]; OR, 0.55 [95% CI, 0.48-0.63], respectively), despite a higher use of BP-lowering medications (OR, 1.21 [95% CI, 1.01-1.45]). Younger patients (<65 years) with established CVD were less likely to be taking CVD preventive medications, but there were no sex differences by area of residence or education level. Large and variable gaps in primary and secondary CVD prevention exist in China, particularly for women. Effective CVD prevention requires an improved overall nationwide strategy and a special emphasis on women with established CVD, who have the greatest disparity and the most to benefit.